Weight and Glycemic Control Outcomes of Bariatric Surgery and Pharmacotherapy in Patients With Melanocortin-4 Receptor Deficiency - Fojas, Esphie Grace Fodra; Radha, Saradalekshmi Koramannil; Ali, Tomader; Nadler, Evan P.; Lessan, Nader (Frontiers in Endocrinology, 2022)
Background Melanocortin-4 receptor (MC4R) mutations are the most common of the rare monogenic forms of obesity. However, the efficacy of bariatric surgery (BS) and pharmacotherapy on weight and glycaemic control in individuals with MC4R deficiency (MC4R-d) is not well-established. We investigated and compared the outcomes of BS and pharmacotherapy in patients with and without MC4R-d. Methods Pertinent details were derived from the electronic database among identified patients who had BS with MC4R-d (study group, SG) and wild-type controls (age- and sex-matched control group, CG). Short- and long-term outcomes were reported for the SG. Short-term outcomes were compared between the two groups. Results Seventy patients were screened for MC4R-d. The SG (6 individuals (4 females, 2 males); 18 (10-27) years old at BS; 50.3 (41.8-61.9) kg/m2 at BS, 3 patients with homozygous T162I, 2 patients with heterozygous T162I, and 1 patient with heterozygous I170V mutations) had follow-up duration up to 10 years. Weight loss which varied depending on mutation type (17.99 (6.10-22.54) %) was stable for 6 months; heterogeneity of results was observed thereafter. BS was found superior to liraglutide on weight and glycaemic control outcomes. At median follow-up of 6 months, no significant difference was observed on weight loss (20.8% vs 23.0%, p=0.65) between the SG and the CG (8 individuals (4 females, 4 males)); 19.0 (17.8-36.8) years old at BS, 46.2 (42.0-48.3) kg/m2 at BS or phamacotherapeutic intervention). Glycaemic control in patients with MC4R-d and Type 2 diabetes improved post-BS. Conclusion Our data indicate efficacious short-term but varied long-term weight loss and glycaemic control outcomes of BS on patients with MC4R-d, suggesting the importance of ongoing monitoring and complementary therapeutic interventions.